2015
DOI: 10.1103/physrevd.92.025038
|View full text |Cite
|
Sign up to set email alerts
|

Supernatural MSSM

Abstract: We point out that the electroweak fine-tuning problem in the supersymmetric Standard Models (SSMs) is mainly due to the high energy definition of the fine-tuning measure. We propose super-natural supersymmetry which has an order one high energy fine-tuning measure automatically. The key point is that all the mass parameters in the SSMs arise from a single supersymmetry breaking parameter. In this paper, we show that there is no supersymmetry electroweak fine-tuning problem explicitly in the Minimal SSM (MSSM) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 148 publications
3
17
0
Order By: Relevance
“…This system can also be used to engineer single photon wavepackets by heralding one photon conditioned on a trigger off of the other. The heralded photon will fall into a pure state if the triggering resolution is much finer than the bi-photon coherence time [34], a condition met by our detection system. We envision that such linear modifications to nonlinear interactions will lead to generation of quantum states of light with exotic coherence properties and benefit applications in continuous variable timefrequency domain quantum information and computing by engineering [35] entanglement of bi-photon and multipartite states.…”
Section: Discussionmentioning
confidence: 99%
“…This system can also be used to engineer single photon wavepackets by heralding one photon conditioned on a trigger off of the other. The heralded photon will fall into a pure state if the triggering resolution is much finer than the bi-photon coherence time [34], a condition met by our detection system. We envision that such linear modifications to nonlinear interactions will lead to generation of quantum states of light with exotic coherence properties and benefit applications in continuous variable timefrequency domain quantum information and computing by engineering [35] entanglement of bi-photon and multipartite states.…”
Section: Discussionmentioning
confidence: 99%
“…[81], and we want to remark it here. Possible exceptions to the above conclusion could be given by models with a high degree of correlations among the high energy parameters, such as in 'supernatural' SUSY scenarios in the context of no-scale supergravity [82][83][84][85], or by models with non-minimal Higgs sectors, e.g. resembling N=2 SUSY [86].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For example, see Table 1 in Ref. [55]. This explains the (so far) non-detection of supersymmetry at the LHC.…”
mentioning
confidence: 99%
“…From the LHC supersymmetry search constraints, it is well known that there exists a supersymmetric electroweak fine-tuning problem in the SSMs. With the GiudiceMasiero mechanism [50], we have shown that the fine-tuning measure defined by Ellis, Enqvist, Nanopoulos, and Zwirner (EENZ) [51] as well as Barbieri and Giudice (BG) [52] is automatically at the order one for the no-scale supergravity and M-theory supergravity, and then the supersymmetric electroweak fine-tuning problem is solved naturally [53][54][55][56]. This is called super-natural supersymmetry.…”
mentioning
confidence: 99%